The Impact of the COVID-19 Pandemic on the Increased Risk of Fraud during Auditing Activities - Lew, Agnieszka (Rewizja finansowa a podwyższone ryzyko oszustwa w czasie pandemii COVID-19, 2022)
The article discusses the issues related to the increased risk of fraud in business units during the COVID-19 pandemic. The aim of the article was to point out the impact of the pandemic on areas that may be exposed to the embellishment of the presented financial data, as well as to show the increased risk during the audit of the financial statement, which must be taken into account by the statutory auditor when performing the financial audit. Possible solutions were identified, also recommended by the Polish regulator, that may help to sensitise the financial and accounting services to the emergence of fraud in enterprises, and in which areas increased caution should be exercised in the analysis of the presented financial data. It was also pointed out how important a role auditors have in building public trust as ethical leaders. The research methods used in the article were a review of source documents and materials issued by international organizations.
Financial Sciences. Nauki o Finansach, 2022, vol. 27, no. 2, s. 25-33
Keywords: financial audit; fraud; audit of financial statements; COVID-19; rewizja finansowa; oszustwo; badanie sprawozdań finansowych